2020
DOI: 10.1093/ageing/afaa123
|View full text |Cite
|
Sign up to set email alerts
|

The clinical usefulness of muscle mass and strength measures in older people: a systematic review

Abstract: Background sarcopenia is the loss of muscle mass and quality and is diagnosed using measures of muscle strength, size and mass. We evaluated the literature on whether sarcopenia measures are predictive of motor outcomes in older people in clinical settings. Methods electronic databases (MEDLINE Ovid, EMBASE, CINAHL and Web of Science) were searched for articles on measures of muscle mass, volume, thickness or strength, in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
(21 reference statements)
1
43
0
Order By: Relevance
“…1A). 6) Although the actual CRWAI is calculated for an entire hospital, the CRWAI score in this study was calcu-lated for each patient to allow comparisons between the two groups (Fig. 1B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). 6) Although the actual CRWAI is calculated for an entire hospital, the CRWAI score in this study was calcu-lated for each patient to allow comparisons between the two groups (Fig. 1B).…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Consequently, a loss of muscle mass is more likely to affect functional outcomes in older men than in older women. 20) Furthermore, several studies have reported an association of hand-grip strength with ADLs 1,3,4,6,19,[22][23][24] that was retained for 1 year after hospital discharge in longitudinal studies. 6) Therefore, hand-grip strength could be a good predictor of ADLs in patients admitted to rehabilitation wards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is how muscle mass and quality indices developed in heathy volunteers can have limited utility in clinical populations which are similar in chronological age, because of markedly diminished muscle mass in clinical cohorts. 73 Clinical trials for hypertension offer an example where there has been a focus on recruiting healthy older people with consequent lack of generalisability to clinical cohorts. Even when the mean age in trials is high, the populations studied are much healthier than typical patients seen in clinic.…”
Section: Developing Capacity In Ageing Researchmentioning
confidence: 99%
“…Specifically, the leg extensor muscle-tendon groups critical for gait [2][3][4] show reduced muscle strength and altered tendon mechanical properties in older, compared to younger adults [5][6][7][8]. Lower limb muscle strength [9][10][11][12], power [11,13,14] and quality [15,16] have been associated with daily life falls incidence in older adults, although findings are not unequivocal [12,13,[17][18][19]. The majority of falls in community-dwelling older adults occur following large balance disturbances (like trips and slips) during walking [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%